Analysis of Policy Implementation to Decline Mother and Infant Mortality Rate Through the Five C's Protocol (Study of East Java Province) - Farida Nurani; Mardiyono Mardiyono; Bambang Supriyono; Andy Fefta Wijaya (e-2477-1929)
AbstractIn policy implementation, constraints are often found. Each region varies according to the context of the society it faces. East Java still has significant Mother Mortality Rate (MMR) and Infant Mortality Rate (IMR) of the low quality of public health, especially in the horseshoe area covering the islands of Madura, Pasuruan, Probolinggo, Situbondo, Bondowoso and Jember. To analyze the policy implementation process, researchers use 5C's Protocol. The results showed that, among the 5 C's which is contained in Content, Context, Commitment, Capacity and Client & Coalition, the Public Health Service as the main actor influences the role of successful implementation of policies and programs. Through the 5C's analysis all stages of the policy process become clear. Beginning the determination of policy issues, implementation methods, monitoring and evaluation of MMR and MMR reduction policies can be explained and illustrated. The existence of a strong line relationship between the five C that will be seen that greatly affect the implementation process of decline policy in MMR and IMR in East Java province. This means that the implementation declining policy of MMR and IMR in East Java through innovation of local government actors and stakeholder involvement encourages the successful implementation of this policy.